2014
DOI: 10.1002/bjs.9481
|View full text |Cite
|
Sign up to set email alerts
|

Duration of antibiotic treatment after appendicectomy for acute complicated appendicitis

Abstract: After appendicectomy for complicated appendicitis, 3 days of antibiotic treatment is equally effective as 5 days in reducing postoperative infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 20 publications
2
53
1
2
Order By: Relevance
“…The overall rate of SSI (6.6%) in this study is consistent with the literature. The rate of OSI in this study, however, is 4.6%, which is higher than that reported by others (1.6-3.1%) [5,8,9]. The relative high number of patients with complex appendicitis in our study could explain this.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The overall rate of SSI (6.6%) in this study is consistent with the literature. The rate of OSI in this study, however, is 4.6%, which is higher than that reported by others (1.6-3.1%) [5,8,9]. The relative high number of patients with complex appendicitis in our study could explain this.…”
Section: Discussioncontrasting
confidence: 56%
“…Although acute appendicitis has a very low mortality rate, surgical site infections (SSI), including superficial SSI (SSSI) and organ space infections (OSI), are the most common complications with an incidence of 2.5-5.4 and 1.3-3.0%, respectively [5,6,7,8,9]. These complications may require re-interventions and are associated with a prolonged hospital stay and increased costs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic appendectomy is an increasing procedure in popularity since initially reported by Semm in 1983 (9). Several studies have shown the advantages of laparoscopic surgery in terms of shorter hospital stay, rapid postoperative recovery, and better pain control (10)(11)(12)(13). However, there have been concerns about the risk of infectious complications, particularly the development of intra-abdominal abscess and superficial wound infection (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…17 In the use of antibiotics area, a clinical trial performed in the Netherlands by Rossem et al established that a 3 day intravenous antibiotic therapy is equally effectively as a 5 day therapy after an appendicectomy secondary to a complicated appendicitis. 18 Despite the use of antibiotics and the peri and post-surgical care, the infection of surgical sites remains the most common complication, delaying by this the primary closure of the wound especially in complicated cases. 19 Reports made in hospitals where the infections are related with suture usage and knot performance are frequently observed.…”
Section: Complicationsmentioning
confidence: 99%